2016
DOI: 10.1111/cns.12557
|View full text |Cite
|
Sign up to set email alerts
|

The E3 Ubiquitin Ligase c‐Cbl Inhibits Microglia‐Mediated CNS Inflammation by Regulating PI3K/Akt/NFκB Pathway

Abstract: In sum, c-Cbl inhibits expression of LPS-stimulated proinflammatory cytokines and chemokines in microglia. We demonstrate an unprecedented role for c-Cbl in microglia-mediated neuroinflammation involving PI3K/Akt/NF-κB pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…RIPK1 inhibitors are being investigated in human clinical trials for neurodegenerative diseases as well, such as ALS and AD, although the precise mechanisms by which RIPK1 kinase activity may contribute to different neurodegenerative conditions remains to be clarified (27,29,30). We show that neuronal, astrocytic, and microglial cultures can undergo RDA in response to TNFα and identify four RDA regulators, c-Cbl, Apc11, Lrrk2, and Nek1, which are highly expressed in the CNS (48,49). Astrocytes in particular express all four genes at high levels, and, interestingly, microglia, which are most sensitive to RDA, are reported to have low expression of RDA suppressor Nek1 (49).…”
Section: Discussionmentioning
confidence: 93%
“…RIPK1 inhibitors are being investigated in human clinical trials for neurodegenerative diseases as well, such as ALS and AD, although the precise mechanisms by which RIPK1 kinase activity may contribute to different neurodegenerative conditions remains to be clarified (27,29,30). We show that neuronal, astrocytic, and microglial cultures can undergo RDA in response to TNFα and identify four RDA regulators, c-Cbl, Apc11, Lrrk2, and Nek1, which are highly expressed in the CNS (48,49). Astrocytes in particular express all four genes at high levels, and, interestingly, microglia, which are most sensitive to RDA, are reported to have low expression of RDA suppressor Nek1 (49).…”
Section: Discussionmentioning
confidence: 93%
“…The NF-κB signaling pathway is involved in regulating inflammation and BBB integrity in cerebral ischemia and neurodegenerative diseases [ 19 , 33 , 34 ]. The PI3K/Akt signaling is well known as a major upstream element of the NF-κB signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of PI3K/Akt/NF-κB pathway is involved in the stabilization of BBB integrity by increasing the expression of tight junction proteins and the alleviation of inflammation via decreasing inflammatory mediators in stroke and neurodegenerative disease [ 17 19 ]. Recent studies showed that Aggf1 possessed the protective roles by activating PI3K/Akt pathway in myocardial ischemia-reperfusion injury and in cell cultures [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…PD in most patients is sporadic, as less than 10% of the patients have a family history. The most important pathological change in PD is the degeneration and death of dopaminergic neurons in the substantia nigra of the midbrain, which leads to the significant decrease in dopamine (DA) content in the striatum 78,79 . Excessive microglial phagocytosis of dopaminergic neurons in the substantia nigra may be an important pathogenic mechanism in the pathological process of PD.…”
Section: Nervous System Disease Related To Pathological Microglial Phmentioning
confidence: 99%